1989
DOI: 10.1007/bf01974282
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting build-up of fungicide resistance in powdery mildew in spring barley

Abstract: In replicate-plot field experiments done in the UK, at one site in Avon for 3 years and another in Warwickshire for 2 years, application of ethirimol or triadimenol sprays or seed treatments was followed by decreases in sensitivity of mildew samples to the particular fungicide applied. Application of ethirimol-triadimenol or tridemorph-triadimenol mixtures caused smaller or no decreases in sensitivity. Differences between isolates in responses to ethirimol and to triadimenol treatment were usually negatively c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…In this case one "at risk" opposes selection against the other. Although a recent modelling exercise showed that a mixture of two high resistance risk partners enhanced the life of both fungicides (Hobbelen et al 2013), experimental evidence supporting use of just "at risk" partners is limited to a few studies ((Brent et al 1989;Lorenz et al 1992;Gisi et al 2005;Thygesen et al 2009). …”
Section: Managing Resistance In Cropsmentioning
confidence: 99%
“…In this case one "at risk" opposes selection against the other. Although a recent modelling exercise showed that a mixture of two high resistance risk partners enhanced the life of both fungicides (Hobbelen et al 2013), experimental evidence supporting use of just "at risk" partners is limited to a few studies ((Brent et al 1989;Lorenz et al 1992;Gisi et al 2005;Thygesen et al 2009). …”
Section: Managing Resistance In Cropsmentioning
confidence: 99%
“…Common yield losses of 11% have been reported (Oerke et al, 1999). A common method of control for this disease is the use of fungicides, but such additional inputs result in increased costs to producers and also possible problems with the development of fungicide-resistant strains in the pathogen population (Brent et al, 1989). The development and deployment of resistant cultivars is another, more environmentally acceptable, means of combating powdery mildew, but can suffer the fate of 'boom and bust' cycles if the resistance is not broad-based (Dreiseitl, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Elysiphe graminis f. sp. hordeil on barley to ethirimol and triadimenol (19,20). Despite the above work, the relationship of the speed of development of resistance to factors such as fungicide dose and frequency of application, mixture or rotation with companion compounds, and use in the eradicant or protectant mode, are still poorly understood, and much further work is justified.…”
Section: Complaint Monitoringmentioning
confidence: 97%
“…Within single fields, it may be possible to collect at different sampling points leaves or fruit bearing lesions, and to obtain viable spores from these in the laboratory. Alternatively, fungicide-treated bait plants can be placed in the field for exposure to the spore population for a particular period and then incubated in a glasshouse or growth room for subsequent disease development and assessment (20). This latter method has the advantage of testing a completely fresh spore population; however, inoculum density in the field can vary greatly according to the weather and microclimate conditions and therefore much replication in terms of sites and exposure events is often necessary in order to give conclusive results.…”
Section: Complaint Monitoringmentioning
confidence: 99%